Management of Patients With Erythropoietic Protoporphyria–Related Progressive Liver Disease. Issue 11 (30th September 2019) - Ardalan, Zaid S.; Chandran, Sujievvan; Vasudevan, Abhinav; Angus, Peter W.; Grigg, Andrew; He, Simon; Macdonald, Graeme A.; Strasser, Simone I.; Tate, Courtney J.; Kennedy, Glen A.; Testro, Adam G.; Gow, Paul J.
Abstract : Erythropoietic protoporphyria (EPP) is an inherited metabolic disorder of heme synthesis resulting from overproduction of protoporphyrin IX (PPIX), which can lead to progressive liver disease characterized by recurrent EPP crises and end‐stage liver disease. We used the Australian Transplant Registry to identify 5 patients referred for liver transplantation between 2008 and 2017. A total of 4 patients had EPP secondary to ferrochelatase deficiency, and 1 patient had X‐linked EPP. No patient had follow‐up with a specialist prior to the diagnosis of progressive liver disease. There were 3 patients who underwent orthotopic liver transplantation, whereas 2 died while on the transplant waiting list. Parenteral PPIX‐lowering therapy was used in 4 patients and was effective in 3 patients, although 2 of these had rebound porphyria and worsening liver function following a decrease in the intensity of therapy. Early disease recurrence in the allograft following transplantation occurred in 2 patients requiring red cell exchange (RCE) to successfully attain and maintain low PPIX levels, but RCE was associated with hemosiderosis in 1 patient. Allogeneic stem cell transplantation (AlloSCT) was performed in 2 patients. One failed engraftment twice, whereas the second rejected the first graft but achieved full donor chimerism with a second graft and increased immunosuppression. In conclusion, our observations suggest that progressive liver disease needs parenteral PPIX‐lowering treatment with the intensity adjusted to achieve a target Erc‐PPIX level. Because EPP liver disease is universally recurrent, AlloSCT should be considered in all patients with adequate immunosuppression to facilitate engraftment. RCE appears to be effective for recurrent EPP liver disease but is associated with an increased risk of iron overload.